Disclosures of audit committees in annual reports. - Seow, Kian Wee. (2008)
In response to the corporate collapse of Amcol, the Stock Exchange of Singapore issued a new Chapter 9B to its Listing Manual on 12 November 1996. The new rules, among other things, introduced more stringent requirements on the independence of audit committee members from the business sector, who felt that some of the proposed changes were too stringent for compliance. Against such a backdrop of events, this study was conducted to find out the nature and extent of the disclosures regarding audit committees in the annual reports of listed companies.